Artificial Intelligence Policies to Enhance Urban Mobility in Southeast Asia - Chong, Yung-Wey; Villanueva-Libunao, Kris; Chee, Su-Yin; Alvarez, Mary Jane; Yau, Kok-Lim Alvin; Keoh, Sye Loong (Frontiers in Sustainable Cities, 2022)
Artificial intelligence (AI) is a powerful tool for technological progress with profound impacts on governments, industries, universities, and societies. In Southeast Asia, AI has presented both opportunities and challenges. Local governments are increasingly experimenting and piloting AI technology to create smart, sustainable, and inclusive cities. Nevertheless, the adoption of artificial intelligence in cities requires proper planning, management, and implementation. Consequently, there is a need for a concerted effort to establish collaboration between industries, governments, academics, and societies in Southeast Asia. This policy brief aims to provide an overview of how artificial intelligence can be implemented to enhance urban mobility in Southeast Asia. To maximize the relevance of the policy brief, experts from various fields have been consulted in its preparation.